Assessing the Role of Clinicopathologic Factors in Outcome Prediction in Subjects Having Oropharyngeal Carcinoma Associated with Human Papillomavirus and Managed with Surgery - Harsh Kumar; Rameet Sandhu; Ritesh Upadhyay; Aanchal Aggarwal; Rathi Rela; Sahana Karthik (Journal of Pharmacy and Bioallied Sciences)
Background: Human papillomavirus (HPV) has been linked as a potential risk factor for increasing incidence of oropharyngeal carcinoma. Aim: The present study aimed to evaluate the role of clinicopathologic factors in outcome prediction in subjects having oropharyngeal carcinoma associated with HPV and managed with surgery. Methods: The present retrospective study assessed data from 54 subjects that were diagnosed with stage III or IV HPV-associated oropharyngeal carcinoma were managed with surgery with or without adjuvant therapy. Results: The mean follow-up duration in the study subjects was 2.7 years. The recurrence-free survival and overall survival rates [age, number of lymph nodes involved, stage of tumor, and Charleston comorbidity index] in the study subjects were 83% and 71% and 62% and 79%, respectively. The recurrence rate in the study was found to be 21%. Conclusion: The conclusion drawn from the present study is that some associated potential risk factors can have lesser relevance in HPV-associated oropharyngeal carcinoma.